The Correlation Between Self-Efficacy and Critical Thinking Skills of Senior High School Students on the Pythagorean Theorem Material - Leni Marlena; Esti Ambar Nugraheni (FKIP Universitas Mataram, 2026)
The objective of the research is to examine the correlation between self-efficacy and mathematical critical thinking skills among senior high school students within the context of the Pythagorean Theorem. Self-efficacy refers to students’ beliefs in their ability to complete learning tasks, while mathematical critical thinking involves analyzing problems, evaluating strategies, and making logical decisions. Employing a quantitative correlational design, the research involved 140 tenth-grade students from a senior high school in Jakarta selected using purposive sampling. Data were collected using a mathematical critical thinking test and a self-efficacy questionnaire. The normality test indicated that the data were normally distributed; therefore, Pearson’s correlation analysis was applied. The results revealed a positive and statistically significant relationship between self-efficacy and students’ critical thinking ability, with a correlation coefficient of r = 0.771 and a significance value of p < 0.01. These findings indicate that higher levels of self-efficacy are associated with stronger mathematical critical thinking skills. The study highlights the importance of fostering students’ self-efficacy as an affective foundation to enhance critical thinking skills and offer meaningful implications for improving teaching and learning practices in secondary education.